The Effect of Digital Media on Pangadereng Values to Improve Students' Digital Ethnopedagogy - Hasni Hasni; Muhammad Syukur; Bahri Bahri; Shabrina Syntha Dewi; Mina Holilah; Nour Muhammad Adrian (International Journal of Social Learning (IJSL), 2025)
This study stems from the importance of preserving local cultural values in the digital age, particularly in social studies learning, through technology-based innovations that support the internalization of Pangadereng values. This study aims to examine the influence of digital media on the transformation and internalization of Pangadereng values (Ade', Bicara, Rapang, Wari', and Sara') to improve the digital ethnopedagogy of junior high school students. This study employed a mixed-methods approach with an exploratory sequential design, incorporating in-depth interviews, participatory observation, and questionnaires. Qualitative data were analyzed thematically, while quantitative data were processed using descriptive statistics and simple linear regression. The findings show that digital media significantly improves students' understanding of Pangadereng values and correlates positively with an increase in digital ethnopedagogy, contributing 38%. Ade' and Sara' show the highest level of internalization, while Bicara, Rapang’, and Wari' require more innovative and context-based pedagogical strategies.